Maxillary central incisor dimensions and its association with lower anterior facial height - Gyawali, Rajesh; Singh, Varun Pratap (Journal of College of Medical Sciences-Nepal, 2016)
Introduction: Maxillary anteriors are the major teeth displayed during the smile and have a dominant role in the dentofacial appearance. As the dimensions of incisors vary with various facial dimensions, this study aimed to find out the ratio of width to height of the maxillary central incisor and correlate it with the lower anterior facial height. Materials and methods: One hundred participants (50 male and 50 female) were enrolled in this study. The width-height ratio of maxillary central incisor was calculated by measurements made in the photographs with Image J software. Lower anterior facial height was measured as the distance between subnasale and lower border of the chin with the help of digital vernier caliper. Correlation between width-height ratio and lower anterior facial height was done with Pearson’s correlation. Results: The width height ratio of maxillary central incisor was found to be 0.86 for male and 0.89 for female. This ratio was statistically insignificant when compared between gender and sides. There was negligible correlation between this ratio and lower anterior facial height. Conclusion: Mean Width-height ratio of maxillary central incisor obtained from this study would serve as a guide in esthetic enhancement of the maxillary anterior dentition.